Analisis Pelaksanaan Pembelajaran Matematika Siswa Kelas V SD 064976 Bandar Selamat - Anisa Nur Suprihatindaria; Dini Puspa Sari; Ira Susanti; Octariani Br Manik; Patika Pratama (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to find how was the implementation of mathematics learning of fifih grade students of SD Negeri 064976 Bandar Selamat. The method used in this study was descriptive naturalistic method. Based on the research findings, it can be concluded that: (1) the implementation of mathematics learning of fifih grade students of SD Negeri 064976 Bandar Selamat Gemolong Sragen has been good because of the implementation of general steps during the learning process; during the mathematics learning process of fifih grade students of SD Negeri 064976 Bandar Selamat, the teacher emphasized much on the concept understanding for the students; the utilization of varied learning media and learning methods could increase the students’ learning activeness; (2) the obstacles found in the mathematics learning process were a) some of the students were lack of enthusiasm in learning mathematics, b) the limited numbers of available learning facilities and learning media, c) the limited time compared to the material that should be taught; (3) the mathematics learning achievements of the students of SD Negeri 064976 Bandar Selamat were quite good